O que é e o que poderia ser: um estudo sobre o conceito de razão de Herbert Marcuse (1936-1955) - Silva, Juliano César da (2010)
This work purposes to investigate the concept of reason in Marcuse‟s thought in the period between 1936 and 1955. It begins by showing that, in most relevant texts of the 1930s, this concept already plays a central role in theoretical-critical project of philosopher. In assessing works of the next decade, it reveals that the reason receive a new outline by the appearance of the term "technological reason", which seems to be a break with the traditional sense of the concept. Finally, it takes the work Eros and civilization demonstrating what Marcuse meant by "libidinal reason" and how this term is an attempt to remain faithful to the original principles of the Critical Theory. This work aims to show also that others concepts always are related of reason one, such as freedom and happiness, and that makes it possible to comprehend how the author criticized the Enlightenment and the prevailing social order while he has been a theorist of revolution and a defender of the union between theory and practice.